Enhancing Early Reading Skills through the Glenn Doman Method Using Flashcards: A Mixed-Methods Study - Winarni, Dian; Budiono; Husamah (Universitas Islam Negeri Raden Intan Lampung, 2026)
Early reading proficiency remains a persistent challenge in Indonesian elementary education, where conventional spelling methods limit multisensory engagement and impede literacy outcomes. Addressing this gap, the Glenn Doman method, grounded in neuroplasticity theory and play-based pedagogy, offers a compelling alternative through structured flashcard stimulation. This study aimed to investigate the implementation process, reading performance outcomes, and pedagogical implications of the Glenn Doman flashcard method among first-grade students at a Muhammadiyah elementary school in East Java, Indonesia. A qualitative descriptive design with embedded quantitative support (pre–posttest) was employed. Data were collected from 122 first-grade students across four classes, four classroom teachers, and one school principal through classroom observations, semi-structured interviews, and document analysis over ten instructional sessions. Average reading scores improved from 51.8% (pretest) to 93.1% (posttest), representing a 41.3% gain across all five literacy indicators. Thematic analysis identified three principal themes: (1) teacher preparedness and adaptive instruction; (2) student engagement through visual and playful learning; and (3) instructional challenges and contextual adaptation. The Glenn Doman method effectively supports early literacy development through multisensory stimulation, joyful repetition, and culturally responsive pedagogical adaptation. The findings offer practical insights for teachers, school administrators, and policymakers engaged in advancing Indonesia's national literacy agenda (GLS) and SDG 4 goals.